THE EFFECT OF CHANGES IN MANAGEMENT, COMPANY SIZE, AUDIT DELAY ON AUDITOR CHANGES IN MANUFACTURING COMPANIES ON IDX 2018-2020 - Widjanarko; Fitri Silvita; Medy Desma (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This study aims to determine the influence of management change, company size and audit delay whether it has a significant effect on auditor turnover in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 (pre-election era, pilpres era & Covid 19 pandemic era). The data used in this study uses secondary data published on the website www.idx.co.id. This study uses quantitative analysis methods, namely with statistics such as regression analysis and classical assumption test. The results showed that management turnover, size and audit delay had no effect on auditor turnover, while company size had a positive effect